The "Goodbye Petrovka" plan: moral economy of file sharing in Post-Soviet Ukraine - Haigh, Maria (Working Paper Series of the Research Network 1989, 2008)
Ukraine, the second most populous of the former Soviet republics, had been named as one of the ten "priority countries" with "unacceptable piracy rates." Kiev's open-air Petrovka Market has become a symbol for the blatant distribution of pirated books, films, music, and software. As living standards and disposable incomes have risen dramatically in recent years, Ukrainians are turning increasingly toward the Internet and to newly-available high bandwidth networks as a new medium for the exchange of music, films, and computer software. Drawing upon the explanatory resources of science studies, particularly the well-established literature on the social construction of technological systems, the author argues that Ukrainians are literally and metaphorically reconstructing imported Internet technologies in accordance with their own culture. To explain this distinctive technological path the author examines the interaction of technologies, users, and regulatory regimes. These have shape